Efficiency of Sewage Treatment Plants in the Sequential Batch Reaktor = Efektywność oczyszczania ścieków w sekwencyjnych reaktorach biologicznych - Jakubaszek, Anita; Stadnik, Artur (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article analyzes the effectiveness of individual Actibloc wastewater treatment plants (produced by Sotralentz) working in the technology of low-rate activated sludge in the Sequential Batch Reactor (SBR) system. The assessment of the effectiveness of household wastewater treatment plants was made on the basis of pollutants: BOD5, COD, total suspended solids, total nitrogen and total phosphorus. The research objects were four household sewage treatment plants located in: Lubań, Kłębanowice, Stara Rzeka and Kościan.
Keywords: sewage treatment system; sequencing batch reactor; monitoring; efficiency; systemy oczyszczania ścieków; sekwencyjny reaktor biologiczny; wydajność